Exploring the reliability of different artificial intelligence techniques in predicting earthquake for Malaysia - Essam Y.; Kumar P.; Ahmed A.N.; Murti M.A.; El-Shafie A. (Elsevier Ltd, 2023)
Acceleration; Decision trees; Disasters; Earthquake effects; Forecasting; Machine learning; Neural networks; Artificial neural network models; Depth; Earthquake; Earthquake acceleration; Ground motion parameters; Input parameter; Machine learning models; Malaysia; Neural-networks; Prediction model; Velocity; acceleration; artificial intelligence; artificial neural network; depth determination; earthquake prediction; ground motion; reliability analysis; seismic velocity; Malaysia; Terengganu; West Malaysia